SARS-CoV-2 infection among asymptomatic healthcare workers of the emergency department in a tertiary care facility - Abdelmoniem, Reham (J Clin Virol, 2021)
BACKGROUND: Healthcare workers (HCWs) represent a high-risk category during the coronavirus disease 2019 (COVID-19) pandemic crisis, with frontline HCWs at emergency departments (EDs) may be at an even higher risk. Determining the spread of infection among HCWs may have implications for infection control policies in hospitals. This study aimed to detect severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection among asymptomatic HCWs of the ED of a large tertiary center in Cairo, Egypt. METHODS: The study was conducted from June 1(st) to June 14(th), 2020. All the recommended national and international indications on infection control measures were followed. Two hundred and three HCWs were included in the study and tested by nasopharyngeal swab (NPS) and rapid serological test (RST). Descriptive statistical analyses were used to summarize the data. RESULTS: Of the 203 HCWs, 29 (14.3 %) tested positive by real-time reverse transcription polymerase chain reaction (RT-PCR). Thirty-seven (18.2 %) HCWs tested positive with RST: 20 with both IgM and IgG; 14 with IgM only, and 3 with IgG only. Age, gender, and/or occupation were not risk factors for SARS-CoV-2 infection. CONCLUSIONS: Point prevalence of COVID-19 in asymptomatic HCWs in ED of tertiary care facility is 14.3 % by RT-PCR. This illustrates the importance of screening all HCWs regardless of symptoms, and the need for strict measures in securing HCWs to reduce transmission from healthcare facilities to the community during the current pandemic.